Climatic Controls on Soil Carbon Accumulation and Loss in a Dryland Ecosystems. Issue 12 (13th December 2021) - Waring, Bonnie G.; Smith, Kenneth R.; Grote, Edmund E.; Howell, Armin; Reibold, Robin; Tucker, Colin L.; Reed, Sasha C.
Abstract: Arid and semiarid ecosystems drive year‐to‐year variability in the strength of the terrestrial carbon (C) sink, yet there is uncertainty about how soil C gains and losses contribute to this variation. To address this knowledge gap, we embedded C‐depleted soil mesocosms, containing litter or biocrust C inputs, within an in situ dryland ecosystem warming experiment. Over the course of one year, changes in microbial biomass and total soil organic C pools were monitored alongside hourly measurements of soil CO2 flux. We also developed a biogeochemical model to explore the mechanisms that gave rise to observed soil C dynamics. Field data and model simulations demonstrated that water exerted much stronger control on soil biogeochemistry than temperature, with precipitation events triggering large CO2 pulses and transport of litter‐ and biocrust‐derived C into the soil profile. We expected leaching of organic matter would result in steady accumulation of C within the mineral soil over time. Instead, the size of the total organic C pool fluctuated throughout the year, largely in response to microbial growth: increases in the size of microbial biomass were negatively correlated with the quantity of C residing in the top 2 cm, where most biogeochemical changes were observed. Our data and models suggest that microbial responses to precipitation events trigger rapid metabolism of dissolved organic C inputs, which strongly limit accumulation of autotroph‐derived C belowground. Accordingly, changes in the magnitude and/or frequency of precipitation events in this dryland ecosystem could have profound impacts on the strength of the soil C sink. Plain Language Summary: Drylands ecosystems play an important role in regulating the global carbon cycle and its feedbacks with climate: they absorb CO2 from the atmosphere in some years, but emit it in others. Most studies examining this year‐to‐year variability focus on how plants respond to climate fluctuations, but desert soils contain even more carbon than the plants do. Here we focused on how variation in weather over the course of a year governs the balance between the stabilization and release of carbon from soils. To do this, we incubated low‐carbon soils in plots that were warmed or maintained at ambient temperature. CO2 release from the soils was monitored continuously for one year, and we periodically examined the distribution of new carbon inputs as they were incorporated into the soil. We found that rain or snowfall stimulated the activity of decomposer microbes belowground, leading to a net release of CO2 and loss of soil carbon, whereas carbon was able to accumulate in the soil during drier periods. Warming had little effect on carbon dynamics. This work gives us a more holistic perspective of carbon cycling in drylands ecosystems. Key Points: We explored the role of climate and carbon input sources in driving intra‐annual variability in soil carbon cycling in a high elevation desert All soil carbon pools and fluxes, including total organic carbon, exhibited substantial temporal variation driven by precipitation events Precipitation triggered rapid microbial metabolism of organic matter, preventing belowground accumulation of carbon inputs